Digital transformation in sports - current trends and trends - Lubysheva L. I. (Theory and Practice of Physical Culture, 2025)
The aim of the study is to identify trends and trends in the digital transformation of the sports industry based on content analysis of current publications of the journal "Theory and Practice of Physical Culture".